2011
DOI: 10.4081/xeno.2011.e4
|View full text |Cite
|
Sign up to set email alerts
|

Enzymatic activity in turkey, duck, quail and chicken liver microsomes against four human cytochrome P450 prototype substrates and aflatoxin B1

Abstract: Cytochrome P450 enzymes (CYP) are a group of monooxygenases able to biotransform several kinds of xenobiotics including aflatoxin B1 (AFB1), a highly toxic mycotoxin. These enzymes have been widely studied in humans and others mammals, but there is not enough information in commercial poultry species about their biochemical characteristics or substrate specificity. The aim of the present study was to identify CYPs from avian liver microsomes with the use of prototype substrates specific for human CYP enzymes a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 23 publications
(24 reference statements)
0
17
0
Order By: Relevance
“…Another P450 enzyme, likely orthologous to mammalian P450 2A6, also converts AFB1 to AFBO in turkeys, chickens, ducks and quail [80][81][82]. However, the specific gene encoding this protein has not been identified in any poultry species [80][81][82][83]. These same studies implicated a P450 1A1 orthologue in AFBO production, which is likely encoded by CYP1A5 in turkeys [78,[80][81][82].…”
Section: Sensitivity: Poultrymentioning
confidence: 99%
“…Another P450 enzyme, likely orthologous to mammalian P450 2A6, also converts AFB1 to AFBO in turkeys, chickens, ducks and quail [80][81][82]. However, the specific gene encoding this protein has not been identified in any poultry species [80][81][82][83]. These same studies implicated a P450 1A1 orthologue in AFBO production, which is likely encoded by CYP1A5 in turkeys [78,[80][81][82].…”
Section: Sensitivity: Poultrymentioning
confidence: 99%
“…Hence, liver is the target organ for AF toxicity (Diaz et al, 2010 andMurcia et al, 2011). Dlimonene, a monoterpenoid constituent of citrus fruit oil (CFO) has inhibitory effects on cytochrome P450 enzymes, p-nitrophenol hydroxylase (pNP) and 7-ethoxyresorufin O-deethylase (EROD) activity in-vitro in liver microsomes, prevents bioactivation of procarcinogens and blocks tumour induction by chemical carcinogens (Reicks and Crankshaw, 1993).…”
Section: Introductionmentioning
confidence: 99%
“…It is possible that the turkey CYP1A5 enzyme cloned by Yip & Coulombe (2006) may in fact correspond to the human CYP1A1 ortholog or, even more interesting, to both the CYP1A1 and 1A2 human orthologs. Murcia et al (2011) found a very high correlation between EROD (CYP1A1/2) and MROD (CYP1A2) activities in turkey liver microsomes (r=0.88, P<0.01) a finding that suggests that CYP1A1 and CYP1A2 activities in turkey liver are catalyzed by the same enzyme (i.e., the avian CYP1A5). The role of CYP1A5 turkey activity on the bioactivation of AFB1 in turkeys is further supported by the work of Guarisco et al (2008) who found that dietary supplementation of the antioxidant butylated hydroxytoluene (BHT) partially protected against the adverse effects of AFB1, an effect that was accompanied by a reduction in EROD and MROD activities in the liver.…”
Section: Wwwintechopencommentioning
confidence: 69%